2019
DOI: 10.1111/ina.12625
|View full text |Cite
|
Sign up to set email alerts
|

HEPA filtration improves asthma control in children exposed to traffic‐related airborne particles

Abstract: Traffic‐related airborne particles are associated with asthma morbidity. The aim of this study was to assess the impact of a high‐efficiency particulate air (HEPA) filtration on the concentrations of traffic particles and the resultant effect on children with asthma. Forty‐three children with asthma were enrolled in this double‐blind, placebo‐controlled crossover design. A HEPA air cleaner or a placebo “dummy” was placed in participants’ homes for four weeks, interrupted by a one‐month washout period, before c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 57 publications
2
21
0
1
Order By: Relevance
“…Our results indicate that NIAPs reduced indoor PM 2.5 levels by 75% (from 29.5 under sham NIAP to 7.5 µg/m 3 under true NIAP). This efficiency of PM 2.5 removal was comparable to those achieved by HEPA‐based or ESP‐based air purifiers 6‐12,25,26 …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our results indicate that NIAPs reduced indoor PM 2.5 levels by 75% (from 29.5 under sham NIAP to 7.5 µg/m 3 under true NIAP). This efficiency of PM 2.5 removal was comparable to those achieved by HEPA‐based or ESP‐based air purifiers 6‐12,25,26 …”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have shown that high‐efficiency particulate air (HEPA) purifiers were effective in reducing indoor PM levels and improving occupants’ cardiopulmonary health 6‐12 . However, the effectiveness of HEPA purifiers relies on regular replacement of filters, which could be costly and time‐consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has several limitations. Firstly, the total study period, including pre-and postintervention periods, was 15 days so that it might be a shorter time to see substantial changes in indoor air condition and participants' health outcomes when compared with other similar studies that had at least 4 weeks [40,45]. However, we observed a 12% significant reduction in the mean PM 2.5 level and some positive outcomes in children with asthma, providing a promising basis for future studies.…”
Section: Discussionmentioning
confidence: 64%
“…This result is consistent with the findings of other intervention studies using HEPA filtration. A study found that indoor PM 2.5 level was reduced from 7.6 μ g/m 3 to 3.4 μ g/m 3 after the HEPA intervention [ 39 ], and another study also reported a significant reduction in PM 2.5 level from 8.0 μ g/m 3 to 4.8 μ g/m 3 with the use of HEPA [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation